From screen to shopping cart: The effect of congruence, wishful identification, and source credibility on live streaming shopping in Indonesia - Raya Notonegoro; Daniel Tumpal Hamonangan Aruan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
Live streaming commerce is a sales channel that is currently often used by business people to market their products, such as fashion products. TikTok is one of the most used live-streaming commerce platforms in Indonesia. Fashion products are a type of product that has a high number of live streamers with high rankings in the live Shopping feature found on the TikTok platform. Seeing the intense competition among live streamers, researchers searched for factors that can influence parasocial relationships, purchase intentions, and consumer behavioral loyalty in the context of live-streaming shopping. The research was conducted using data obtained from 350 respondents who are active users of TikTok and have watched live-streaming shopping on TikTok. Data were obtained using the non-probability sampling method by distributing online surveys. The results of the tests show that all hypotheses are supported by the data obtained, except those related to the influence of attractiveness and expertise on parasocial relationships or unilateral relationships felt by consumers towards live streamers in live streaming commerce TikTok. This research contributes to business people and live streamers, especially related to growing parasocial relationships, purchase intentions, and behavioral loyalty of TikTok Live consumers.